2018
DOI: 10.1177/2309499018812236
|View full text |Cite
|
Sign up to set email alerts
|

Independent assessment and outcomes of 196 short-tapered stems short-term follow-up and review of the literature

Abstract: Background: Longer term outcome data are now becoming available for short-tapered femoral stems for cementless total hip arthroplasty. The shorter stem has a metaphyseal fit, loading the bone in this area, leading to physiological bone remodelling. It is also bone preserving, as it is 35 mm shorter. It may be easier to insert through a smaller incision and potentially reduce complication rates. We present a retrospective single surgeon case series of 196 patients (>53% follow-up over 5 years). All patients had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
5
0
3
Order By: Relevance
“…13 Available literature on short stems shows a heterogenous picture. Some stems have proven to be reliable in the short term, 14 while studies of others showed varied results. 15 Early studies of the Proxima stem have focused on surgical technique, 16 migration pattern and bony integration using radiostereometric analysis and/or dual energy X-ray absorptiometry (DXA).…”
Section: Discussionmentioning
confidence: 99%
“…13 Available literature on short stems shows a heterogenous picture. Some stems have proven to be reliable in the short term, 14 while studies of others showed varied results. 15 Early studies of the Proxima stem have focused on surgical technique, 16 migration pattern and bony integration using radiostereometric analysis and/or dual energy X-ray absorptiometry (DXA).…”
Section: Discussionmentioning
confidence: 99%
“…It is increasingly accepted that preserving bone stock is essential in case of revision surgery and should potentially reduce complications such as loosening of the stem or periprosthetic fracture due to less bone resorption [ 46 ]. Furthermore, short-stem implants have proven to be a safe and efficient procedure that has demonstrated good primary stability and osteointegration and therefore a low risk of aseptic loosening despite their smaller surface area and implant-bone interface [ 12 , 28 , 47 , 48 ]. On the other hand, the surgical technique requires precision and experience to avoid misalignment, incorrect sizing of the stems and intraoperative fracture and is related with a steep learning curve [ 30 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…La Taperloc Microplasty™ (Zimmer-Biomet, Warsaw-Indiana, USA) fait partie des tiges raccourcies (3,5 cm de moins que la Taperloc™ standard) et a été développée par Lombardi à la fin des années 2000 [13]. Les études à court terme qui ont été publiées sur cette tige sont peu nombreuses et rapportent des résultats très satisfaisants [14][15][16][17]. Sauf erreur de notre part, nous n'avons pas retrouvé dans la littérature de résultats à plus de 5 ans de recul et sur des séries de plus de 100 cas.…”
Section: Introductionunclassified
“…Toutes les valeurs de p ont été comparées avec une valeur alpha de 0,05 pour rechercher une différence significative. Compte tenu du fait qu'il s'agissait d'une étude mono-centrique et mono-opérateur tous les dossiers étaient complets en pré et en postopératoire pour toutes les variables analysées.Le score de PMA est passé de 11 ± 2,3[5][6][7][8][9][10][11][12][13][14][15][16][17] en préopératoire à 17,8 ± 0,8 [12-18] au recul maximum (p=0,00001) avec un score douleur moyen de 5,9 ± 0,4. Il n'y avait pas de douleur de cuisse susceptible d'être en relation avec la tige.…”
unclassified